Estilos de afrontamiento y su afectación en el estrés, bienestar psicológico en un adulto de 50 años de la ciudad de Babahoyo - Sánchez Rodríguez, Melanye Janeth (2022)
The coping styles that human beings have are among the main survival characteristics, which promotes the development of temperament either positively or negatively, as well as the behavior they reproduce in society according to the event they have to face. When these coping styles do not have a control system the individual is exposed to experience health problems both physically and mentally; this case study has as a priority the objective of analyzing whether coping styles cause effects on stress and psychological well-being of a 50 year old adult resident of the city of Babahoyo; the respective collection of information and total approach of the case has the necessary psychological resources organized among; methods, techniques, application of psychological batteries such as: the perceived stress scale, the Rosemberg self-esteem scale, the mental well-being scale. It should be noted that to further deepen the case based on the scientific arguments on the variables also has an extensive bibliographical research, on the other hand presents the structural diagnosis of the pathology found, after all the methodological process applied in the patient of 50 years which was a generalized anxiety disorder-F41.1, according to the criteria of the diagnostic manuals DSM-5 and ICD-10. Finally, in order to reduce the symptoms of the pathology found, the psychotherapy of the cognitive behavioral approach (CBT) is applied so that the patient can improve her lifestyle and new positive alternatives of coping.